A toxic shot from the hip. Issue 3 (2nd July 2010) - Oomen, Judith W P M; Smits, Bart W; Swinkels, Dorine W; Schreurs, Berend W; Bloem, Bastiaan R; Hendriks, Mathijs P
Abstract : A 26-year-old man developed a movement disorder characterised by bradyphrenia, bradykinesia, rigidity, tremor and dystonia, several years after having been shot by a gun in the hip. Laboratory investigations revealed anaemia and porphyria. The authors demonstrate that his neurological condition was a delayed manifestation of lead toxicity, caused by slow absorption of lead from persisting bullet fragments in the hip joint. Treatment with excision of the femoral head and debridement of the hip followed by a total hip, in combination with chelating therapy, led to a remarkable remission.